2017
DOI: 10.1111/1440-1681.12877
|View full text |Cite
|
Sign up to set email alerts
|

Case‐control pharmacogenetic study of HCN1/HCN2 variants and genetic generalized epilepsies

Abstract: Epilepsy is a common complex neurological disorder, and some forms are resistant to drug treatment. The HCN1/HCN2 genes encode hyperpolarization-activated cyclic nucleotide-gated channels, which play important roles in the electrophysiology of neurons. We investigated the association between HCN1/HCN2 variants and drug resistance or the risk of genetic generalized epilepsies (GGEs). We used matrix-assisted laser desorption/ionization time-of-flight mass spectrometry to assess nine variants of HCN1/HCN2 in 284 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…During the last few years, accumulated evidence supports the strong role of genetics in unexplained DRE patients . Moreover, advances in clinical testing technology have increased the diagnostic yield from 10% a few years ago to 30%‐40%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last few years, accumulated evidence supports the strong role of genetics in unexplained DRE patients . Moreover, advances in clinical testing technology have increased the diagnostic yield from 10% a few years ago to 30%‐40%.…”
Section: Introductionmentioning
confidence: 99%
“…During the last few years, accumulated evidence supports the strong role of genetics in unexplained DRE patients. [7][8][9][10] Moreover, advances in clinical testing technology have increased the diagnostic yield from 10% a few years ago to 30%-40%. This increase has primarily been technology-driven, due to the development of nextgeneration sequencing (NGS).…”
mentioning
confidence: 99%
“…It is the gene responsible for coding the H channel, subunit number 2, for activated cations by cyclic nucleotide and for hyperpolarization, [21][22][23] has high sensitivity to cAMP modulation, and is located especially in the thalamus and trunk region. Studies have identified modifications in HCN2 Gs rs7255568 and rs3752158 alleles in genetically generalized epilepsies (GGEs) determined, regarding to controls (p=0.039, p=0.027, respectively).…”
Section: Hcn2mentioning
confidence: 99%
“…Studies have identified modifications in HCN2 Gs rs7255568 and rs3752158 alleles in genetically generalized epilepsies (GGEs) determined, regarding to controls (p=0.039, p=0.027, respectively). 21 Only rs7255568 was linked to risks of childhood absence epilepsy (CAE) (p=0.028) and juvenile myoclonic epilepsy (JME) (p=0.02). 21 While rs3752158 is linked to the risk of generalized tonic-clonic seizures, JME and febrile seizures, in all C and GC + CC alleles.…”
Section: Hcn2mentioning
confidence: 99%
See 1 more Smart Citation